Validation of a fully automated chemiluminescent immunoassay for cattle serum and plasma progesterone measurement - Megahed, Ameer A.; Jones, Kristi L.; Bisinotto, Rafael S.; Chebel, Ricardo C.; Galvão, Klibs N.; Chan, Ann M.; Bittar, João H. J. (Frontiers in Veterinary Science, 2023)
Monitoring circulating progesterone concentration ([P4]) is an important component of basic and applied reproduction research and clinical settings. IMMULITE® 2000 XPi (Siemens Healthineers, Cary, NC) is a newly upgraded fully automated immunoassay system marketed for human use to measure concentrations of different measurands, including P4. Our objective was, therefore to characterize the analytical performance of the IMMULITE® 2000 XPi P4 immunoassay (IPI) across the reportable range in serum and plasma of cattle. The IPI validation protocols included characterization of the method linearity, within-run, and between-run precision through calculation of the coefficient of variation (CV). The method accuracy was assessed through the calculation of the spiking-recovery (SR) bias across the reportable range (0.2 – 40 ng/mL). Passing-Bablok regression and Bland-Altman plots were used to determine the interlaboratory bias for two laboratories. Three types of observed total error (TEo) were calculated based on the considered type of bias, TEoSR (spiking-recovery), TEoRB (range-based bias), and TEoAB (average-based bias). The IPI was linearly related to the true value (R2 = 0.997) across the reportable range. The within-run and between-run precision (CV%) of the IPI for both serum and plasma [P4] of clinical relevance (1, 2, 5, and 10 ng/mL) were <5% and <10%, respectively. The TEo reported here for serum and plasma at [P4] of 1 and 5 ng/mL was ~20% and ~25%, respectively. Of interest, the three types of TEo were relatively similar regardless of the considered bias. We concluded that the automated IPI provides a precise, accurate, reliable, and safe method for measuring [P4] in both serum and plasma of cattle. Consistent with the manufacturer's recommendations, the serum matrix is more accurate than plasma.